2014
DOI: 10.1016/j.ijscr.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy with preservation of gastric tube blood flow after esophagectomy: Report of a case

Abstract: HighlightsWe performed a pancreaticoduodenectomy in which the gastroduodenal artery was preserved.The patient who had previously undergone esophagectomy, was diagnosed as middle bile duct cancer.In order to prevent gastric tube ischemia, the gastroduodenal artery and gastroepiploic artery had to be preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…No. Our case 79 M PHC Metachoronous 11 RGEA, RGEV, RGA, RGV 5y2m, recurrent free, alive Okimoto et al 2014 70 M BDC Metachoronous 10 RGEA, RGEV, RGA, RGV Not described [ 3 ] Nandy et al 2014 70 M PHC Metachoronous 3 Not described Dead, <1y [ 4 ] Addeo et al 2011 73 M mRCC Metachoronous 6 RGEA, RGEV Not described [ 5 ] Fraguilidis et al 2011 50 M PHC Metachoronous 13 RGEA 1y2m, liver metastasis, alive [ 6 ] Ikeda et al 2006 61, 63 M BDC Metachoronous 10 RGEA, RGEV, RGV 1y, recurr...…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…No. Our case 79 M PHC Metachoronous 11 RGEA, RGEV, RGA, RGV 5y2m, recurrent free, alive Okimoto et al 2014 70 M BDC Metachoronous 10 RGEA, RGEV, RGA, RGV Not described [ 3 ] Nandy et al 2014 70 M PHC Metachoronous 3 Not described Dead, <1y [ 4 ] Addeo et al 2011 73 M mRCC Metachoronous 6 RGEA, RGEV Not described [ 5 ] Fraguilidis et al 2011 50 M PHC Metachoronous 13 RGEA 1y2m, liver metastasis, alive [ 6 ] Ikeda et al 2006 61, 63 M BDC Metachoronous 10 RGEA, RGEV, RGV 1y, recurr...…”
Section: Discussionmentioning
confidence: 86%
“…Following a PubMed search using the keyword “PD after esophageal cancer”, 11 case reports were found, 7 of which were by Japanese authors ( Table 1 ). In 5 of the cases [ [3] , [4] , [5] , [6] , [7] ], the primary disease was pancreatic head cancer and bile duct cancer in 2 cases each and metastatic renal cell carcinoma in 1 case. The prognosis was clearly described for 3 cases with 1 patient each dying in less than a year, surviving over a year and surviving over 14 months.…”
Section: Discussionmentioning
confidence: 99%
“…Several guidelines have been designed to provide the best recommendation for nonoperative management in those with low risk for malignancy and to identify and recommend resection for those with overt or latent malignancy. 1,2 With the increase in the detection of pancreatic cysts, a larger number of patients are being studied. New radiographic and clinical features associated with high risk for malignancy are being described and incorporated in the guidelines since the Sendai criteria.…”
Section: Isolated Intraductal Papillary Mucinous Tumor Arising In The...mentioning
confidence: 99%
“…When typical PD is performed, GDA is ligated and cut for complete resection of the lymph node. 2,3 However, for PD patients who have undergone gastric tube reconstruction, it is necessary to perform a special procedure to maintain blood flow to the gastric tube. Inoue et al 4 reported 3 different surgical approaches: (1) PD with GDA and RGEA preservation; (2) PD with divisions of both, GDA and RGEA/V, after microvascular reconstruction; or (3) PD with divisions of GDA and RGEA/V, removal of the gastric tube, and reconstruction with the small or large intestine.…”
mentioning
confidence: 99%
See 1 more Smart Citation